Assessing labour strength in Serbia, Croatia and Slovenia: How to explain the differences? - Kosović, Nikola; Copîl, Daria (The European Journal of Applied Economics, 2016)
This paper assesses the current strength of labour unions in Serbia, Croatia and Slovenia and elaborates on the main factors that have led to the current situation. The first part of the paper includes an in-depth literature review of the current state-of-the-art in assessing the labour strength across Europe, with special emphasis on post-communist countries. The second part of the paper provides the assessment of labour union strength in the surveyed countries. The authors argue that there are significant differences in the roles of labour movements. Serbia and Slovenia quite differ, with extremely weak and extremely strong labour movements, respectively, while Croatia is located in between. Kosović and Copîl also elaborate on the causes of such weaknesses. They identify four main factors: communist legacy, nationalistic elites, economic crisis and foreign influence, and the lack of trust among citizens, and conclude that it is impossible to explain such a complex issue as labour strength by observing any of these factors separately. However, taken together, they all provide a quality explanation of the current union strength in the observed countries.